The Lyrical Figuration as Mechanism of Representation in César Vallejo’s Fabla salvaje - Mudarra Montoya, Américo (2019)
Under the modernista model of writing, this text presents motifs related to the uncanny, the unforeseen, the unexpected; a world where the rational explanations fail to give satisfactory answers. One of the pillars of such constructions is determined by the uncanny, the perplexity proposed by the represented world. Faced with certainty, this story proposes a disturbing world.